Student Science Process Skill (KPS) In Animal Phycsiology Laboratory Experiment (EDUCATIO : Journal of Education, 2018)
Research on Science Process Skill (KPS) in Animal Physiology Laboratory Experiment for one semester has been conducted. The aim of this research was gaining the best proportion of KPS parameters during mid and final exam with guided inquiry method. The 4th semester students of Biology Education, FKIP UnPak who took Animal Physiology Laboratory Experiment had role as the respondents. Observation worksheets for individu among groups have been distributed. Hereafter, questionnaire information by online system also been collected. The result showed the highest Science Process Skill (83%) parameter was doing an experiment. Meanwhile, the lowest (68,75%) was construct a hypothesis. It also supported by positive spirit from students when doing experiments. It can be concluded that Animal Physiology Laboratory Experiment with guided inquiry method was well programed for KPS development.